SEJARAH PERKAPALAN TRADISIONAL DI BAGANSIAPIAPI - Muhklis Afandi; Isjoni Isjoni; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrackt :.Indonesia is known as the world's largest maritime or archipelago country with 70% of its territory consisting of sea. So many of the islands that exist in Indonesia is separated by the sea. But it is not a barrier to connect between one island with another island. In this case, the sea transportation capital is closely related to connecting the islands. Traditional ship or boat is one of the maritime culture that since prehistoric times has played an important role in human life in the world including Indonesia. Later in Bagansiapiapi (Rokan Hilir) also famous as the largest traditional shipbuilding in Indonesia before independence. The Bagansiapiapi artificial vessel is perfect for accessing different types and features in Java, Nusa Tenggara and Maluku. The purpose of writing is to make reconstruction of the past in a systematic and obejektif with data collection and processing so menghsilkan quality research, as for the purpose of this writing is as follows: (1) To know the history of traditional shipping in Bagansiapiapi. (2) To know the process of making traditional ship Bagansiapiapi (3) To know the characteristics of traditional ships in Bagansiapiapi(4) To know the development and distribution of traditional vessels in Bagansiapiapi. This study authors use qualitative methods, which is a qualitative method is an approach that focuses on the general principles underlying the embodiment of a phenomenon that exists in human life or better known by the patterns. The history of traditional shipping in Bagansiapiapi originated from ethnic Chinese or Chinese inputs at Bagansiapiapi in 1928. The number of pagoda in Bagansiapiapi area as their place of worship, this proves that ethnic Chinese have long been settled compared to other ethnicities. It is expected that the local government of Rokan Hilir Regency can give attention to traditional shipyard industry in Bagansiapiapi.Keywords: History of Traditional Ships